D09 Exploring neurodegeneration and inflammation blood biomarkers in a cohort of italian patients with Huntington's disease. (12th September 2022) - Lazzaro, Giulia Di; Zinzi, Paola; Picca, Anna; Petracca, Martina; Solito, Marcella; Lo Monaco, Maria Rita; Grandolfo, Anna Sofia; Calabresi, Paolo; Bentivoglio, Anna Rita
Abstract : Background: Huntington's disease (HD) is a hereditary neurodegenerative disorder due to CAG expansion in HTT gene. Recently, inflammation received great attention with focus on potential biomarkers to follow disease onset and progression, helping to understand underlying pathophysiological mechanisms. Aims: To measure blood levels of neurodegeneration and inflammation biomarkers and their correlation with clinical and demographic data. Materials and Methods: 39 HD patients followed at our outpatient service were consecutively enrolled. Clinical assessment included UHDRS TMS&TFC, MMSE, PBAs. Serum levels of selected biomarkers (Neurofilament light chain, BDNF, IL-1β, IL5, IL-6, IFN, TNF-a, IL4 and IL10) were essayed using commercially available kits on an ELLA™ automated immunoassay system. Results: IL-1b and IL 17 serum levels negatively correlated with TFC (respectively rho=-0.423, p=0, 022 and rho=- 0, 548, p=0.002) while IL-4 (rho=0.381, p=0.05), IL-17 (rho=0.419, p=0.001), TNF-a (rho=0.427, p=0.019), IL-6 (rho=0.495, p= 0.01) correlated with higher TMS scores. Disease duration positively correlated with serum levels of IL-17 (rho =0.460, p=0.008), TNF-α (rho=0.367, p=0.042), IL-6 (rho=0.417, p=0.021). NFL level positively correlated with burden of pathology (BOP) (p=0.04, rho 0.43). Interestingly, we also found a positive correlation of BDNF and TMS (p=0.023, rho=0.407), possibly a manifestation of a compensatory mechanism. A linear regression model with TMS score as dependent variable and TNF-a, NfL, BDNF and IL6 as independent variables was able to explain the 49, 9% of the variance, (p=0.004). Conclusion: This study confirms the association between serum NfL and BOP with tendency to manifest a pro-inflammatory status along with disease progression (higher TMS and longer disease duration).